Parliamentary Communication Allowances: Good for Nothing?. (August 2021) - Umit, Resul
In many countries, members of parliament receive publicly funded allowances to communicate with the electorate. Some hope that ensuing parliamentary communication engages the people with politics and increases electoral participation. Others worry that such use of public funds might create an unfair advantage for incumbents and affect electoral results. Yet, the consequences of this practice remain unknown. Data from the UK House of Commons suggest that both the hopes and the worries are baseless: there is no evidence that parliamentary communication allowances increase electoral turnout or affect incumbents' vote share. If these allowances are not effective, both parliaments and their members might want to reconsider their use and usefulness.